Equivalent chemical substitution in double–double perovskite-type ALaLiTeO6:Mn4+ (A = Ba2+, Sr2+, Ca2+) phosphors enabling wide range crystal field strength regulation and efficient far-red emission. Issue 11 (24th February 2023) - Huang, Jinmei; Jiang, Pengfei; Cheng, Zien; Qin, Jie; Cong, Rihong; Yang, Tao
Abstract : A small A-cation in the ALaLiTeO6 :Mn 4+ phosphors leads to a compact structure and MnO6 -octahedron, further resulting in a redshift in luminescence spectra and a remarkable enhancement in quantum efficiency and thermal stability. Abstract : Mn 4+ -activated phosphors have shown wide prospective applications in phosphor-converted white light-emitting diodes (pc-WLEDs) and pc-LEDs used in illumination and indoor plant cultivation, respectively. Recently, double perovskites A2 B′B′′O6 with a tunable crystal structure and versatile octahedral sites have been extensively studied as good host matrixes for Mn 4+ -emitters to realize tunable far-red emissions. Herein, a series of double-double perovskite-type ALaLiTeO6 :Mn 4+ (A = Ba, Ba0.5 Sr0.5, Sr, Sr0.5 Ca0.5, Ca) phosphors were synthesized and structurally characterized, and the correlations between their structure and luminescence were also studied systematically. With a decrease of the A-cation size, an increased distortion in the average structure and a structure symmetry lowering ( I 2/ m → P 21 /n ) were observed for ALaLiTeO6 :Mn 4+ . In contrast, on the local scale, the degree of (Li/Te)O6 -octahedral distortion is positively correlated with the Δ IR value, which is the ionic radius difference between A 2+ and La 3+ . The local structural changes were found to be irrelevant to the significant improvements in photoluminescence properties. In combination with careful spectroscopic analysis, we deciphered that a decreased A-cation is in fact helpful for the enhancements in crystal field strength ( D q / B = 2.12–2.82) and Mn–O covalent bonding, thereby resulting in an improved quantum efficiency, a suppressed nonradiative transition, and a redshift in photoluminescence spectra. Amongst the ALaLiTeO6 :Mn 4+ phosphor series, CaLaLiTeO6 :Mn 4+ exhibits the highest external quantum efficiency of 70.1% and internal quantum efficiency of 96.4% and superior thermal stability (93.3%@423 K), making CaLaLiTeO6 :Mn 4+ very promising as far-red phosphors for pc-LEDs. The findings of this work will serve as a new guide for rational design of high-performance Mn 4+ -activated double-double perovskite-type far-red phosphors.